Empirical Determinants of Government Efficiency: A Study Based on Objective Indicators - Guedes de Oliveira, Francisca (2012)
This paper is concerned with two things: finding an objective and easily quantifiable measure of government efficiency and testing possible determinants of such quality. As measures of government efficiency we use the ratios of infant mortality rate to health expenditures as a percentage of GDP and the ratios of drop out and illiteracy rates to education expenditures as a percentage of GDP. We assume that government efficiency in providing health and education services depends on economic, political and cultural factors.